2015
DOI: 10.1093/infdis/jiv301
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of p-IκBα Ubiquitylation by Autophagy-Related Gene 7 to Regulate Inflammatory Responses to Bacterial Infection

Abstract: Loss of Atg7 switched binding of p-IκBα from Atg7 to Ub, resulting in increased ubiquitylation of p-IκBα and intensified inflammatory responses against K. pneumoniae. Our findings not only reveal a regulatory role of Atg7 in ubiquitylation of p-IκBα but also indicate potential therapeutic targets for K. pneumoniae control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Macroautophagy is not only induced by intracellular bacteria, but also can be activated by extracellular bacteria such as Pseudomonas aeruginosa and Klebsiella pneumoniae, which may involve complex mechanisms. [885][886][887] Furthermore, macroautophagy can be induced by all intracellular and extracellular Gram-negative bacteria via a common mechanism involving naturally produced bacterial outer membrane vesicles; 888,889 these vesicles enter human epithelial cells, resulting in autophagosome formation and inflammatory responses mediated via the host pathogen recognition receptor NOD1. 888 Viruses can also be targeted by autophagy, and in turn can act to inhibit autophagy.…”
Section: O Vacuole Import and Degradation Pathwaymentioning
confidence: 99%
“…Macroautophagy is not only induced by intracellular bacteria, but also can be activated by extracellular bacteria such as Pseudomonas aeruginosa and Klebsiella pneumoniae, which may involve complex mechanisms. [885][886][887] Furthermore, macroautophagy can be induced by all intracellular and extracellular Gram-negative bacteria via a common mechanism involving naturally produced bacterial outer membrane vesicles; 888,889 these vesicles enter human epithelial cells, resulting in autophagosome formation and inflammatory responses mediated via the host pathogen recognition receptor NOD1. 888 Viruses can also be targeted by autophagy, and in turn can act to inhibit autophagy.…”
Section: O Vacuole Import and Degradation Pathwaymentioning
confidence: 99%
“…Previous studies showed that autophagy played specific roles in degrading intracellular pathogens in a cell-autonomous manner and orchestrating systemic immunoinflammatory responses by regulating the immune system and inflammation [ 57 ]. Silence of Atg genes caused heavier bacterial burdens of macrophages, and deletion of Atg genes in plants and Drosophila increased viral replication, mortality, and more severe pathological phenotypes [ 60 , 61 ]. Knockout of Atg7 increased tissue injury and inflammatory responses, especially maturation and secretion of IL-1 β and activation of pyroptosis [ 15 ].…”
Section: Autophagy-related Protein 7 and Pyroptosis In Sepsismentioning
confidence: 99%
“…The ubiquitin activating enzyme E1-like protein/autophagy related 7 (GSA7/ATG7) is a multifunctional protein, which requires for mitophagy and contributes to regulation of mitochondrial quantity and quality by eliminating the mitochondria to a basal level to achieve cellular energy requirements and preventing excess ROS production as well as modulates TP53 activity to regulate cell cycle and survival during metabolic stress [15,[31][32][33]45]. We have shown that glutamine deprivation suppresses ATG7 mRNA expression independent of IRE1 knockdown.…”
Section: Fig 3 Comparative Effect Of Glutamine Deprivation On the Ementioning
confidence: 99%
“…Thus, autophagy inhibition by Baf A1 or knockdown of ATG7 or ATG12 induced cytotoxicity in multiple human bladder cell lines. Induction of apoptosis was found in cells with autophagy inhibition [32]. Whereas ATG7 loss leads to the expected decrease in autophagic flux, it also results in endoplasmic reticulum stress, accumulation of dysfunctional mitochondria, oxidative stress, activation of AMPK, and a marked decrease in protein synthetic capacity [33].…”
mentioning
confidence: 99%
See 1 more Smart Citation